Impulse Computerkunst : Graphik - Plastik - Musik - Film. - Franke, Herbert W.; Leibniz, G.W.; Zuse, Konrad (München : Goethe-Institut, 1971)
Adrian, Marc ; Alsleben, Kurd ; Beckmann, Otto ; Citron, Jack P. ; Compro ; Computer Technique Group ; Fetter, William A. ; Grassl, Alfred ; Laposky, Ben F. ; Mezei, Leslie ; Nees, Georg ; Noll, Michael ; Palyka, Duane M. ; Schroeder, Manfred R. ; Sutcliffe, Alan
biog. p. 27-35
Duits
Impulse Computerkunst : Graphik - Plastik - Musik - Film, Deutsche Bibliothek, Brussel, 15 février 1971 - 6 mars 1971
boek